BIMSTEC headquarters: the hub of Indo-Pacific corridor - Anisha, Anika Tabassum Ahmed (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2015.